Estimation of Black Carbon Emission of China - Lu, Yiqiong (Journal of Environmental Accounting and Management, 2026)
With a strong absorption effect of solar radiation, black carbon is deemed as one of the important causes of climate change, and also one of the factors resulting in fog and haze, significantly affecting the quality of atmospheric environment and human health. It’s mainly produced by incomplete combustion of carbonaceous substances and has become one of the hot issues in studies of climate change and atmospheric environmental quality in recent years. It is difficult to measure black carbon aerosol emissions directly, and we usually estimate black carbon emission roughly by applying emission factors obtained in the laboratory for the real atmosphere. By using black carbon emission factors of industries published at home and abroad recently, this article estimated black carbon emissions from 2000 to 2012 in China, which was growing from 928.58Gg to 1527.56Gg. In this paper, black carbon emissions were compared in various industries, of which the amount of black carbon emissions of residential activities occupied the largest proportion, but declined gradually each year, while the emission of industry took the second place with an increasing trend every year, and the proportion of emission of transport sector grew ina fast pace from 5.65% in 2000 to 10.51% in 2012.